Religious Experiences of Muslim Students Who are Addicted to Online Games in Rural Areas in Countries with A Muslim Majority - Fahrizal, Yanuar; Andrea, Ririn (GLOBAL HEALTH SCIENCE GROUP, 2024)
Internet gaming habits may influence teenagers' religious conduct. Gamers are able to survive without doing other activities by sitting for long periods. Many gamers who are hooked to online games are more concerned with the game than with their worship, causing them to get further from God. This study seeks to investigate the spiritual experiences of Yogyakarta students addicted to online games. This study employs a qualitative, phenomenological methodology. Data gathered from eight participants through snowball sampling underwent analysis using the Giorgi method. The study highlights diverse spiritual experiences among online game-addicted students, including parental and student indifference, shifts in activities, pupils' appreciation for spirituality, neglect of religious activities, and integration of internet games and worship for problem-solving. Excessive online gaming results from various factors, yielding varied spiritual experiences, enabling students to understand spirituality's significance and act as problem-solvers.